Preparation of graphene oxide and multi-walled carbon nanotubes, and they are used to modify the glassy carbon electrode for sensing Enalapril Maleate - Adil Abdulzahra Rashak; Faiq F. Karam (Results in Chemistry, 2024)
In this study, the graphene oxide and multi-walled carbon nanotubes fabrication was evaluated using (SEM), (FTIR), Raman spectroscopy and (XRD). The results showed promising accuracy for the graphene oxide and multi-walled carbon nanotubes voltammetric sensor. The direct voltammetric determination of Enalapril Maleate in pharmaceutical samples, urine, and serum is detailed using a straightforward and extremely sensitive technique. Graphene oxide-multiwall carbon nanotubes are added to glassy carbon electrodes in an efficient manner to activate the GO-MWNT structures, which then electrocatalyzes the reduction of Enalapril Maleate. The results of the cyclic voltammetric (CV) experiment showed that the electrocatalytic activity of GO-MWNTs to reduce Enalapril Maleate was significantly improved, leading to a much higher cathodic peak current for EM. This finding opens the door to the possibility of creating a very sensitive voltammetric sensor to detect EM in biological and pharmaceutical fluid samples. A linear calibration curve in the 2.5–12.5 ppm concentration range, a detection limit of 0.2 ppm, and a relative standard deviation (R.S.D.%) lower than 1.0 % (n = 5) were all indicative of ideal conditions. Lastly, EM is a diffusion-controlled process that proceeds through a two-electron-two-proton change, which provides a mechanism for the reduction of EM.. The GO-MWCNTs/GCE sensor had a good repeatability and excellent reproducibility, R.S.D.% =1.77 and 1.82.